Cost-effective and simple biodiesel production process from waste cooking oil using a rotating tube reactor: Kinetic study and techno-economic analysis - Jarungwongsathien, A.; Chanthon, N.; Ngaosuwan, K.; Kiatkittipong, W.; Wongsawaeng, D.; Mens, W.; Chin, Bridgid; Yusup, S.; Quitain, A.T.; Assabumrungrat, S. (Elsevier, 2025)
This study presents an efficient method for biodiesel production using a rotating tube reactor (RTR). The continuous production process from various feedstocks was simulated based on experimental data and kinetic modeling, and further evaluated to assess its economic feasibility. NaOH catalyzed transesterification of waste cooking oil (WCO) in the RTR was aligned in the pseudo-first order of WCO with an activation energy of 27.81 kJ/mol and pre-exponential factor of 3.76 × 103 min−1 (R2 = 0.9996). The continuous RTR can reduce FFA from 6 to 1.89 wt% via esterification of WCO. Turbulent Taylor vortex flow regime indicated that transesterification of WCO in the RTR required higher mixing intensity to achieve a high biodiesel yield of 89.72 % within 11.23 min. The RTR approach offers a comparable total capital investment to existing intensified methods while reducing operating costs, underscoring its potential for cost-effective biodiesel production. The economic evaluation indicated that biodiesel from high-FFA content WCO was more favorable, with a short payout period of only 3.1 years, a high net present value of 34.8 million USD, and an internal rate of return of 82.6 %. The RTR proves to be a viable, simple, and flexible solution for biodiesel production from various feedstocks.